Are You Keeping an Eye on Me? The Influence of Competition and Cooperation on Joint Simon Task Performance - Mendl, Jonathan; Fröber, Kerstin; Dolk, Thomas (Frontiers in Psychology, 2018)
Social interaction plays an important role in human life. While there are instances that require cooperation, there are others that force people to compete rather than to cooperate, in order to achieve certain goals. A key question is how the deployment of attention differs between cooperative and competitive situation; however, empirical investigations have yielded inconsistent results. By manipulating the (in-)dependence of individuals via performance-contingent incentives, in a visual go-nogo Simon task the current study aimed at improving our understanding of complementary task performance in a joint action context. In the independent condition each participant received what s/he achieves; in the cooperative condition each participant received the half of what both achieved, and in the competitive condition participants were instructed that the winner takes it all. Extending previous findings, we found sequential processing adjustments of the Simon effect as a function of the interdependency (i.e., competition, cooperation) and transition between (i.e., go-nogo requirements) interacting individuals. While sequential processing adjustments of the Simon effect in both the competition and cooperation condition were unaffected when alternating between responsible actors (i.e., nogo-go transition), sequential processing adjustments were enlarged under competition for repeating responsibilities of one and the same actor (i.e., go-go transitions). In other words, the prospect of performance-contingent reward in a competitive context exclusively impacts flexible behavioral adjustments of one’s own actions. Rather than fostering the consideration and differentiation of the other actor, pushing one’s own performance to the limit appears to be the suitable strategy in competitive instances of complementary tasks. Therefore, people keep their eyes on themselves when aiming at beating a co-actor and emerging as the winner.